Lunch Box Innovation Product Design In The Millennial Era - Bayu Pranoto; Hilmi Iman Firmansyah; Hangga Wicaksono; Muhammad Fakhruddin; Rilis Eka Perkasa (Universitas Sebelas Maret, 2021)
Almost all kids still bring a lunch box and a bottle of water in their bag when they go to school. His mother always prepares a lunch box complete with a drinking water bottle, hoping that his son can enjoy his favorite lunch and avoid starvation. Sometimes the mother is distraught when the child has brought the lunch box, but the water bottle is left behind. Then the mother was willing to take her child's water bottle to her school. This is certainly not expected by either the mother or the child. As a form of concern for the author to this problem, the author proposes a lunch box design with a lunch box lid that also functions as a drinking water bottle. The idea of this design proposal is one grab. Both are food & drink in your hand. The goal is how to make kids can grab their food and drink quickly and practice. So, it is proposed to modify the top cover of the standard food pack to become a drink bag. The design process begins with analyzing market needs, making sketches, creating 3D design models using the Autodesk Inventor application, material selection, and product evaluation.